Mister Exam
Lang:
EN
EN
ES
RU
Other calculators:
Integral Step by Step
Derivative Step by Step
Differential equations Step by Step
How to use it?
Limit of the function
:
Limit of (6^(2*x)-7^(-2*x))/(-2*x+sin(3*x))
Limit of x^(4/x)
Limit of e^(3-x)*(-2+x)
Limit of ((4+x^2+5*x)/(7+x^2-3*x))^x
Graphing y =
:
4+x
Derivative of
:
4+x
Integral of d{x}
:
4+x
Identical expressions
four +x
4 plus x
four plus x
Similar expressions
4-x
Limit of the function
/
4+x
Limit of the function 4+x
at
→
Calculate the limit!
v
For end points:
---------
From the left (x0-)
From the right (x0+)
The graph:
from
to
Piecewise:
{
enter the piecewise function here
The solution
You have entered
[src]
lim (4 + x) x->5+
lim
x
→
5
+
(
x
+
4
)
\lim_{x \to 5^+}\left(x + 4\right)
x
→
5
+
lim
(
x
+
4
)
Limit(4 + x, x, 5)
Lopital's rule
There is no sense to apply Lopital's rule to this function since there is no indeterminateness of 0/0 or oo/oo type
The graph
0
2
4
6
8
-8
-6
-4
-2
-10
10
-20
20
Plot the graph
Other limits x→0, -oo, +oo, 1
lim
x
→
5
−
(
x
+
4
)
=
9
\lim_{x \to 5^-}\left(x + 4\right) = 9
x
→
5
−
lim
(
x
+
4
)
=
9
More at x→5 from the left
lim
x
→
5
+
(
x
+
4
)
=
9
\lim_{x \to 5^+}\left(x + 4\right) = 9
x
→
5
+
lim
(
x
+
4
)
=
9
lim
x
→
∞
(
x
+
4
)
=
∞
\lim_{x \to \infty}\left(x + 4\right) = \infty
x
→
∞
lim
(
x
+
4
)
=
∞
More at x→oo
lim
x
→
0
−
(
x
+
4
)
=
4
\lim_{x \to 0^-}\left(x + 4\right) = 4
x
→
0
−
lim
(
x
+
4
)
=
4
More at x→0 from the left
lim
x
→
0
+
(
x
+
4
)
=
4
\lim_{x \to 0^+}\left(x + 4\right) = 4
x
→
0
+
lim
(
x
+
4
)
=
4
More at x→0 from the right
lim
x
→
1
−
(
x
+
4
)
=
5
\lim_{x \to 1^-}\left(x + 4\right) = 5
x
→
1
−
lim
(
x
+
4
)
=
5
More at x→1 from the left
lim
x
→
1
+
(
x
+
4
)
=
5
\lim_{x \to 1^+}\left(x + 4\right) = 5
x
→
1
+
lim
(
x
+
4
)
=
5
More at x→1 from the right
lim
x
→
−
∞
(
x
+
4
)
=
−
∞
\lim_{x \to -\infty}\left(x + 4\right) = -\infty
x
→
−
∞
lim
(
x
+
4
)
=
−
∞
More at x→-oo
One‐sided limits
[src]
lim (4 + x) x->5+
lim
x
→
5
+
(
x
+
4
)
\lim_{x \to 5^+}\left(x + 4\right)
x
→
5
+
lim
(
x
+
4
)
9
9
9
9
= 9.0
lim (4 + x) x->5-
lim
x
→
5
−
(
x
+
4
)
\lim_{x \to 5^-}\left(x + 4\right)
x
→
5
−
lim
(
x
+
4
)
9
9
9
9
= 9.0
= 9.0
Rapid solution
[src]
9
9
9
9
Expand and simplify
Numerical answer
[src]
9.0
9.0
The graph